2021
DOI: 10.1111/ijcp.14811
|View full text |Cite
|
Sign up to set email alerts
|

Value of shear wave elastography in predicting hepatorenal syndrome in patients with liver cirrhosis and ascites

Abstract: Acute renal impairment is a common complication in patients with liver cirrhosis and is associated with high rates of morbidity and mortality. Patients usually present acute kidney injury (AKI) without renal structural changes. The major causes of AKI include prerenal, intrinsic/parenchymal disorders, obstructive nephropathy and hepatorenal syndrome (HRS). 1-3 Among these, HRS is a special form of renal impairment characterised by rapid progression and poor prognosis. It is reported that HRS has an extremely p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The authors found that decreased baseline renal stiffness can predict kidney injury in patients with advanced liver disease and ascites alongside increased serum cystatin C, urinary NGAL, and RARI. In this study, the combination of SWE and the renal artery resistive index improved the ability to predict the occurrence of HRS, with an AUROC of 0.89 [79].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 70%
See 1 more Smart Citation
“…The authors found that decreased baseline renal stiffness can predict kidney injury in patients with advanced liver disease and ascites alongside increased serum cystatin C, urinary NGAL, and RARI. In this study, the combination of SWE and the renal artery resistive index improved the ability to predict the occurrence of HRS, with an AUROC of 0.89 [79].…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 70%
“…14, x FOR PEER REVIEW 10 of 14 combination of SWE and the renal artery resistive index improved the ability to predict the occurrence of HRS, with an AUROC of 0.89[79].…”
mentioning
confidence: 99%
“…Such differentiation is crucial not only for guiding optimal treatment decisions but also for avoiding unnecessary volume expansion and the adverse effects of vasoconstrictor medication. While many studies have shown higher RRI values in HRS patients compared to non-AKI patients, there is a lack of studies focusing on RRI’s performance in ATN-AKI scenarios[ 7 - 9 ]. For instance, a small study by Maroto et al [ 8 ] reported significantly higher RRI in AKI patients compared to non-AKI patients (mean RRI: 0.74 vs 0.64).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced cirrhosis often exhibit elevated RRI due to renal vascular constriction. Some studies have explored the utility of RRI in assessing renal dysfunction in cirrhosis patients, particularly in determining whether AKI is structural or functional[ 7 , 8 ]. Fang et al [ 7 ] observed higher RRI values in patients with HRS compared to those with ATN.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation